Co-activation of the diaphragm and external intercostal muscles through an adaptive closed-loop respiratory pacing controller - Adury, Rabeya Zinnat; Siu, Ricardo; Jung, Ranu (Frontiers in Rehabilitation Sciences, 2023)
Respiratory pacing is a promising alternative to traditional mechanical ventilation that has been shown to significantly increase the survival and quality of life after the neural control of the respiratory system has been compromised. However, current pacing approaches to achieve adequate ventilation tend to target only the diaphragm without pacing external intercostal muscles that are also activated during normal inspiration. Furthermore, the pacing paradigms do not allow for intermittent sighing, which carries an important physiological role. We hypothesized that simultaneous activation of the diaphragm and external intercostal muscles would improve the efficiency of respiratory pacing compared to diaphragm stimulation alone. Hence, we expanded an adaptive, closed-loop diaphragm pacing paradigm we had previously developed to include external intercostal muscle activation and sigh generation. We then investigated, using a rodent model for respiratory pacing, if simultaneous activation would delay the fatigability of the diaphragm during pacing and allow induction of appropriate sigh-like behavior in spontaneously breathing un-injured anesthetized rats (n=8) with pacing electrodes implanted bilaterally in the diaphragm and external intercostal muscles, between 2 nd and 3 rd intercostal spaces. With this novel pacing system, we show that fatigability of the diaphragm was lower when using combined muscle stimulation than diaphragm stimulation alone (p=0.014) and that combined muscle stimulation was able to induce sighs with significantly higher tidal volumes compared to diaphragm stimulation alone (p=0.014). Our findings demonstrate that simultaneous activation of the inspiratory muscles could be used as a suitable strategy to delay stimulation-induced diaphragmatic fatigue and to induce a sigh-like behavior that could improve respiratory health.